Antigenicity and immunogenicity of Plasmodium vivax merozoite surface protein-3 - Bitencourt, A; Vicentin, E; Jimenez, M; Ricci, R; Leite, J; Costa, F; Ferreira, L; Russell, B; Nosten, F; Rénia, L; Galinski, MR; Barnwell, J; et al. (Public Library of Science, 2013)
A recent clinical trial in African children demonstrated the potential utility of merozoite surface protein (MSP)-3 as a vaccine against Plasmodium falciparum malaria. The present study evaluated the use of Plasmodium vivax MSP-3 (PvMSP-3) as a target antigen in vaccine formulations against malaria caused by P. vivax. Recombinant proteins representing MSP-3α and MSP-3β of P. vivax were expressed as soluble histidine-tagged bacterial fusions. Antigenicity during natural infection was evaluated by detecting specific antibodies using sera from individuals living in endemic areas of Brazil. A large proportion of infected individuals presented IgG antibodies to PvMSP-3α (68.2%) and at least 1 recombinant protein representing PvMSP-3β (79.1%). In spite of the large responder frequency, reactivity to both antigens was significantly lower than was observed for the immunodominant epitope present on the 19-kDa C-terminal region of PvMSP-1. Immunogenicity of the recombinant proteins was studied in mice in the absence or presence of different adjuvant formulations. PvMSP-3β, but not PvMSP-3α, induced a TLR4-independent humoral immune response in the absence of any adjuvant formulation. The immunogenicity of the recombinant antigens were also tested in formulations containing different adjuvants (Alum, Salmonella enterica flagellin, CpG, Quil A,TiterMax® and incomplete Freunds adjuvant) and combinations of two adjuvants (Alum plus flagellin, and CpG plus flagellin). Recombinant PvMSP-3α and PvMSP-3β elicited higher antibody titers capable of recognizing P. vivax-infected erythrocytes harvested from malaria patients. Our results confirm that P. vivax MSP-3 antigens are immunogenic during natural infection, and the corresponding recombinant proteins may be useful in elucidating their vaccine potential.